Unveiling soil-transmitted helminth infections and associated risk factors in rural primary schoolchildren in Malaysia - SN, Mohd Johari; PY, Tan; Radhika, Loganathan; Yvonne Ai Lian, Lim; KT, Teng; SC, Lee; KR, Selvaduray; Romano, Ngui (Malaysian Society of Parasitology and Tropical Medicine., 2024)
Soil-transmitted helminths (STHs) are known as one of the neglected parasitic diseases, leading to significant health issues and associated complications. This study aims to assess the current prevalence of STH infections and the associated risk factors among rural primary schoolchildren in Malaysia. A cross-sectional study was conducted among 638 schoolchildren (7-11 years old) from 10 rural primary schools in five regions of Malaysia. The overall prevalence of STH infections among schoolchildren was 54.5%, with T. trichiura being the predominant STH species (50.9%), followed by A. lumbricoides (19.6%) and hookworms (7.4%). The highest prevalence of STH infections was recorded in the schools in Perak (96.6%), followed by Pahang (85.4%), Johor (42.1%) and Sabah (6.2%). At the same time, none of the schoolchildren in Sarawak were infected with STHs. The findings also highlighted that the older age group (10-11 years old) exhibited a higher prevalence of STH infection and T. trichiura compared to those aged 7-9 years old (P = 0.01) among the schools with a high prevalence of STH infections (> 70%). Several variables, such as being female (1.9 [1.2, 3.0]) (Adjusted odd ratio [95% confidence interval]), low household income (30.9 [7.0, 136.5]), using untreated water supply (1.9 [1.1, 3.2]), indiscriminate defaecation (1.9 [1.1, 3.1]), indiscriminate garbage disposal (2.8 [1.3, 6.0]), eating with hands (5.9 [3.4, 10.4]) and experiencing pallor signs (2.3 [1.1, 5.0]), emerged as significant predictors of STH infections in this study population. The present study underscores that in specific rural community areas of Malaysia, STH infections continue to pose health concerns among primary schoolchildren. Hence, to ensure the sustained effectiveness of the measures taken to control STH infections, a collaborative and ongoing effort between various stakeholders is imperative to provide targeted support to rural communities, especially those in areas lacking essential amenities and healthcare services.